Dactylorhizahatagirea: A Critical Issue for Research and Development in Nepal - Magar, Manu Maya; Dhital, Shambhu Prasad; Yamada, Tetsuya; Pun, Umed Kumar (Nepal Journal of Science and Technology, 2020)
Dactylorhiza hatagirea (D. don), commonly known as ‘Panchaule’ in Nepal, is a terrestrial orchid found in temperate to the alpine region. It is valued for its ornamental and medicinal use. It is collected haphazardly from nature due to high economic demand. However, its propagation is limited in nature due to its non-endospermous seeds requiring mycorhizal fungal association for germination. This limitation is leading to the extinction of this orchid from nature and has been enlisted as an endangered and threatened species. Its collection and trade are restricted but have been prioritized for research, conservation, and agro-technology development. As very few research has been reported in D. hatagirea, found in Nepal, intensive research, propagation, reintroduction, and commercial cultivation will help control the rhizome collection from nature and meet the economic demand. It will help in the identification and conservation of our local germplasm through its diversity study at the molecular and revenue generation through commercial cultivation under artificial conditions. In this review paper, we discuss the limited research and developments conducted in Dactylorhiza at various levels and ways forward for its research, conservation, and utilization. As the plant is valued for its biochemical constituents, modern biotechnological tools such as transcriptomics and metabolomics can be best utilized to explore the opportunities and increase its production and reintroduction through mass propagation for better commercialization and conservation.